Temporalities of oxytocin for labour augmentation: a mixed-methods study of time factors shaping labour practices in a busy maternity unit in Tanzania - Monica Lauridsen Kujabi; Luzango Maembe; Daniel Nkungu; Nanna Maaløe; Brenda Sequeira D'mello; Jos van Roosmalen; Thomas van den Akker; Flemming Konradsen; Kidanto Hussein; Eunice Pallangyo; Morten Skovdal; Jane Brandt Sørensen (BMC, 2024)
Abstract Background High rates of labour augmentation with oxytocin have been found in some low- and lower-middle-income countries, causing potential perinatal harm. It is critical to understand the reasons for this overuse. Aim was to explore factors that shape practices around using oxytocin for labour augmentation in a high-volume labour ward in Dar es Salaam, Tanzania. Methods Mixed-methods data collection was conducted from March 2021 to February 2022, including structured observations of 234 births, 220 h of unstructured labour ward observations and 13 individual in-depth interviews with birth attendants. Thematic network analysis and descriptive statistics were used to analyse data. We used a time-lens to understand practices of oxytocin for labour augmentation in time-pressured labour wards. Results Birth attendants constantly had to prioritise certain care practices over others in response to time pressure. This led to overuse of oxytocin for augmentation to ensure faster labour progression and decongestion of the, often overburdened, ward. Simultaneously, birth attendants had little time to monitor foetal and maternal condition. Surprisingly, while oxytocin was used in 146 out of 234 (62.4%) structured labour observations, only 9/234 (4.2%) women had active labour lasting more than 12 h. Correspondingly, 21/48 (43.8%) women who were augmented with oxytocin in the first stage of labour had uncomplicated labour progression at the start of augmentation. While the partograph was often not used for decision-making, timing of starting oxytocin often correlated with natural cycles of ward-rounds and shift-turnovers instead of individual women's labour progression. This resulted in co-existence of 'too early' and 'too late' use of oxytocin. Liberal use of oxytocin for labour augmentation was facilitated by an underlying fear of prolonged labour and low alertness of oxytocin-related risks. Conclusions Time scarcity in the labour ward often made birth attendants deviate from clinical guidelines for labour augmentation with oxytocin. Efforts to navigate time pressure resulted in too many women with uncomplicated labour progression receiving oxytocin with little monitoring of labour. Fear of prolonged labour and low alertness to oxytocin-mediated risks were crucial drivers. These findings call for research into safety and benefits of oxytocin in low-resource settings and interventions to address congestion in labour wards to prevent using oxytocin as a time-management tool.